Hubungan Pendidikan dan Tingkat Pengetahuan yang Menyebabkan Pemberian MP-ASI Sebelum Bayi Berusia 6 Bulan di Puskesmas Distrik Pelebaga - Lili Farlikhatun; Emma Emmy Yoku (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT A preliminary study at the Pelebaga District Health Center in November 2024 showed that out of 150 infants aged 0-6 months, 95 infants (63%) received exclusive breastfeeding, while 55 infants (37%) had been given early complementary feeding. A survey on November 13, 2024 found that out of 10 mothers, 7 (70%) had given complementary feeding before the baby was 6 months old. This shows that the practice of early complementary feeding is still high. In fact, exclusive breastfeeding is the best nutrition for infants up to 6 months old without additional food or drink, except for medicines, vitamins, or minerals. After 6 months, complementary feeding is given gradually. To determine the relationship between education and level of knowledge that causes complementary feeding before the baby is 6 months old at the Pelebaga District Health Center in 2024. This study uses a quantitative method with an observational design and a cross-sectional approach, which measures independent and dependent variables simultaneously. Shows that mothers with Poor Knowledge mostly Provide Complementary Feeding as many as 9 respondents (15%) and Do Not Provide Complementary Feeding as many as 1 respondent (1.7%). While mothers with Good Knowledge mostly Do Not Provide Complementary Feeding as many as 47 respondents (78.3%) and those who Provide Complementary Feeding as many as 3 respondents (5%). The results of the statistical test obtained a P-Value .001 (p 0.05) which means that there is a relationship between knowledge and the provision of complementary feeding to infants under 6 months of age at the Pelebaga District Health Center. The OR value = 30,850, shows that mothers with poor knowledge have a 30,850 times greater tendency to provide complementary feeding to infants under 6 months of age compared to mothers with good knowledge. The OR value = 30,850, shows that mothers with poor knowledge have a 30,850 times greater tendency to provide complementary feeding to infants under 6 months of age compared to mothers with good knowledge. Pelebaga District Health Center is expected to improve routine education on the importance of exclusive breastfeeding and the risks of early complementary feeding, as well as provide lactation consultation services and guidance on providing complementary feeding that is appropriate for the baby's age. Keywords: Education, Knowledge, Providing Complementary Feeding Before the Baby is 6 Months Old.ABSTRAK Studi pendahuluan di Puskesmas Distrik Pelebaga pada November 2024 menunjukkan dari 150 bayi usia 0-6 bulan, 95 bayi (63%) mendapatkan ASI eksklusif, sedangkan 55 bayi (37%) telah diberikan MP-ASI dini. Survei pada 13 November 2024 menemukan dari 10 ibu, 7 (70%) telah memberikan MP-ASI sebelum bayi berusia 6 bulan. Hal ini menunjukkan masih tingginya praktik MP-ASI dini. Padahal, ASI eksklusif adalah nutrisi terbaik untuk bayi hingga usia 6 bulan tanpa tambahan makanan atau minuman lain, kecuali obat, vitamin, atau mineral. Setelah 6 bulan, pemberian MP-ASI dilakukan secara bertahap. Mengetahui hubungan pendidikan dan tingkat pengetahuan yang menyebabkan pemberian MP-ASI sebelum bayi berusia 6 bulan di Puskesmas Distrik Pelebaga tahun 2024. Penelitian ini menggunakan metode kuantitatif dengan desain observasional dan pendekatan cross-sectional, yang mengukur variabel independen dan dependen secara bersamaan. Menunjukkan bahwa ibu yang memiliki Pengetahuan Kurang mayoritas Memberikan Mp-ASI sebanyak 9 responden (15%) dan Tidak Memberikan Mp-ASI sebanyak 1 responden (1.7%). Sedangkan ibu dengan Pengetahuan Baik mayoritas Tidak Memberikan Mp-ASI sebanyak 47 responden (78.3%) dan yang Memberikan Mp-ASI sebanyak 3 responden (5%). Hasil uji statistik didapatkan nilai P-Value .001 (p 0,05 ) yang artinya terdapat adanya hubungan antara pengetahuan dengan pemberian MP-ASI pada bayi usia kurang dari 6 bulan di Puskesmas Distrik Pelebaga. Nilai OR = 30.850, menunjukkan bahwa ibu yang berpengetahuan kurang memiliki kecenderungan 30.850 kali lebih besar memberikan MP-ASI pada  bayi  usia  kurang dari 6 bulan dibandingkan dengan ibu yang berpengetahuan baik. Nilai OR = 30.850, menunjukkan bahwa ibu yang berpengetahuan kurang memiliki kecenderungan 30.850 kali lebih besar memberikan MP-ASI pada  bayi  usia  kurang dari 6 bulan dibandingkan dengan ibu yang berpengetahuan baik. Puskesmas Distrik Pelebaga diharapkan meningkatkan edukasi rutin tentang pentingnya ASI eksklusif dan risiko MP-ASI dini, serta menyediakan layanan konsultasi laktasi dan panduan pemberian MP-ASI yang sesuai usia bayi. Kata Kunci: Pendidikan, Pengetahuan, Pemberian MPASI Sebelum Bayi Berusia 6 Bulan.